Women's Perspectives on (Post)Migration Between Literature, Arts and Activism - Between Africa and Europe. - Borst, Julia; Neu-Wendel, Stephanie; Tauchnitz, Juliane (2023)
This volume takes a closer look at women's perspectives on (post-)migration and explores the uncertainties, frictions, struggles and opportunities emerging from that context. It revolves around African and Afrodescendant female writers and artists and refers to the uncomfortable stories they tell, stories about what it means to have migrated to, live in, or have been born in Romance-speaking Europe. Their voices reveal positionings of the 'female Other' that oscillate between alienation and belonging, moving between African, European and other (diasporic) spaces.